Bilingual Translation System (BTS) / Razlin Dawina Abdul Razak - Razlin Dawina , Abdul Razak (2002)
Educational tools have evolved tremendously over the past few years. Educational tools used to be restricted to anything involving pen and paper, it is not so now. With the introduction of computers, the way things are handled and conducted in society has changed. The educational field is not excluded. Parents and educators are aware of the impact of computers on our lives and the lives of their children. Computer usage have been integrated with learning. Therefore more and more educational programs are being developed each day. The Bilingual Translation System (BTS) is a stand-alone system. It is a translation system where English words are translated to other languages. It is to be used like a dual language dictionary. It is expected to cater the students who are learning a foreign language as well as by the lecturer of that language. In Malaysia, getting revision and reference materials including dictionaries for foreign languages is not an easy task. With the introduction of this package, it is hoped that local students will no longer have difficulty in finding a translation system.